Pengaruh Pemberian Pupuk Kotoran Walet Terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis Gueneensis Jacq) di Pre Nursery - Boren; Prima Novia; Bustari Badal (Jurnal Research Ilmu Pertanian, 2024)
This research was carried out in the koto Panjang Ikur village, Koto tangah District, Padang city, West Sumatra Provience. This research starts in January-April 2022. The objective of the study was to obtain a comparison of the best growing media from the application of swallow droppings fertilizer on the growth of oil palm (elaeis guineensis jacq) seedlings in the pre nursery. This experiment used a completely randomized design (RAL) with 4 treatments and 6 replications, so there were 24 experimental units. Each experimental units. Each experimental unit consisted of 6 polibags, so there were 144 polybags. The treatment is as follows : A = Top Soil, B = Top Soil : Swallow manure fertilizer (1:1), C = Top Soil : Swallow manure fertilizer (2:1). Observational data were analyzed statistically with variance (f test). If f count > from f table 5%, proceed with duncans new multiple range test (DNMRT) test at 5% significance level. Variables observed were seedling height. Number of leaves (midrib), tuber diameter, top fresh weight, top dry weight, root length, root fresh weiht, root dry weight, and visual observation. From the experimental results it was concluded that the application of swallow manure fertilizer had a very significantly different effect on the increase in seedling height, number of leaves . hump diameter, upper fresh weight, upper dry weight, root length, fresht root weight, and was not significantly different in weightdry roots. The ratio of Top Soil : Swallow manure fertilizer (1:2) is the best ratio for the growth of oil palm seedlings (elaeis guineensis jacq) in the pre nursery when compared to other treatments